Catalyst Comparison for Additive-Free Acceptorless Dehydrogenation of Indoline Derivatives - Stubbs, James M.; Nanuwa, Amrit S.; Hoffman, Matthew D.; Blacquiere, Johanna M. (Synlett, 2023)
A group of thirteen catalysts of type [Ru(Cp/Cp*)(P–P)(MeCN)]PF6, bearing cooperative or noncooperative bidentate phosphine ligands, were evaluated for the catalytic acceptorless dehydrogenation of indoline. The systematic comparison revealed that the optimal cooperative catalyst structure included a Cp ancillary ligand, and an N,N-disubstituted P,P-disubstituted 1,5-diaza-3,7-diphosphacyclooctane ligand, denoted as (PR2NR′2). A cooperative complex bearing a PPh2NPh2 ligand exhibited about a twofold longer lifetime than a noncooperative analogue with (diphenylphosphino)ethane (dppe) as the supporting bisphosphine ligand. The cooperative catalyst effectively dehydrogenated a range of indoline substrates to give substituted indoles.
Keywords: cooperative catalysis; dehydrogenation; indoles; ruthenium catalysis; ligands